Outburst behavior of the dwarf nova CG Draconis. Issue 3 (24th January 2023) - Usatov, Maxim; Shears, Jeremy
Abstract: During the British Astronomical Association (BAA) 2022 campaign, 27, 436 photometric observations of the dwarf nova (DN) CG Draconis were made, with 106 eclipses recorded. This work summarizes the new data available and provides updated ephemeris and commentary on the observed eclipse profiles. The orbital period found is P orb = 4 h 31 m 38 s ± 1 s $$ P_{orb}={4}^{h}{31}^{m}{38}^{s}± {1}^{s} $$ . Two types of quasi‐periodic outbursts are identified: normal outbursts, of Δ V ≈ 1.25 $$ Δ V≈ 1.25 $$ mag amplitude, and bright, of Δ V ≈ 1.5 $$ Δ V≈ 1.5 $$ mag. The pattern resembles superoutbursts of SU UMa‐type DNe, however, no presence of superhumps characterizing these DNe was found. Given CG Dra is located above the period gap, it may represent a new intermediary subtype between SS Cyg and SU UMa‐type stars, or provide support to superoutburst models that do not rely on eccentric accretion disks.